Are cities different? Patterns of species richness and beta diversity of urban bird communities and regional species assemblages in Europe. Issue 4 (6th November 2013) - Ferenc, Michal; Sedláček, Ondřej; Fuchs, Roman; Dinetti, Marco; Fraissinet, Maurizio; Storch, David
Abstract Aim To compare macroecological patterns between bird communities of European cities and regional species assemblages in the surrounding landscape, and to reveal geographical trends in the urbanization of native avifauna. Location Forty‐one towns and cities in continental Europe. Methods We compiled data on the species richness and community composition of urban avifauna from 41 European city breeding bird atlases, and of species assemblages comprising nine grid cells (each about 50 km × 50 km) from the EBCC Atlas of European Breeding Birds (hereafter regional assemblages). Species–area relationships (SARs), latitudinal trends in diversity and the distance decay of community similarity were compared using regression models (generalized linear models). Observed urban communities were compared with randomly assembled ones to reveal systematic effects of the urban environment on native bird communities across Europe. We employed variance partitioning to quantify the relative effect of environmental parameters and the spatial position of cities on species richness. Results The species–area relationships did not differ significantly between cities and regional assemblages. Species richness of both types of communities increased towards higher latitudes, although the relationship was unimodal for regional assemblages, in contrast to cities. The increase in beta diversity with distance was on average less pronounced in cities than in regional assemblages, and was lower between individual cities than between communities of the same size randomly drawn from regional species assemblages. Moreover, average beta diversity was lower in northern cities, which are characterized by a relatively higher proportion of species from regional species pools. Main conclusions The species–area relationship and latitudinal trends are largely congruent between cities and the regional assemblages. However, city avifaunas tend to be relatively more uniform across space, revealing biotic homogenization. Urban communities in northern cities are more uniform as a higher proportion of bird species breeds in cities.